Pengaruh Beban Pajak Tangguhan dan Perencanaan Pajak terhadap Manajemen Laba pada Perusahaan Sektor Teknologi dan Sektor Healthcare di Bursa Efek Indonesia Tahun 2019 – 2023 - Evi Zumrotul Bustani; Made Dudy Satyawan (Jurnal Riset Ekonomi dan Akuntansi, 2025)
The research conducted aims to determine the effect of deferred tax burden and tax planning on profit management in technology sector companies and healthcare sector companies listed on the Indonesia Stock Exchange (IDX). The research conducted used a period of 5 periods starting in 2019-2023. The population used includes the entire technology sector and healthcare sector listed on the Indonesia Stock Exchange (IDX) in 2019-2023. The technique used in taking the sample used a purposive sampling technique with criteria set by the researcher so that a sample size of 31 companies was obtained. The type of data used is secondary data obtained from the Indonesia Stock Exchange (IDX) website. The use of research data analysis methods is in the form of multiple linear regression analysis. The conclusion of this study shows that Deferred Tax Burden has an effect on Profit Management. While Tax Planning has no effect on Profit Management.